Pengaruh Solvabilitas dan Corporate Social Responsibility (CSR) Terhadap Manajemen Laba pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi tahun 2018-2020 - Hesti Setiorini; Dinal Eka Pertiwi; Marini Marini; Yusmaniarti Yusmaniarti (UNIVED Press, 2023)
This study aimed to determine the effect of solvency and corporate social responsibility (CSR) on earning managementof manufacturing companies in the consumer goods industry sector listedon the stock exchange in 2018-2020. This study used a quantitative method by using secondary data. The sample of this used a purposive samplingmethod with a population of manufacturing companies in the consumer goods industry sector listed on the Indonesia stock exchange in 2018-2020. The techniques of analyzing of thie study used multiple linier regression techniques to test the hypothesis by using the SPSS program. The result of this study show that solvency has no effect on earnings management and corporate social responsibility (CSR) also has no effect on eraning management.